COST AND EFFICIENCY OF RICE FIELD FARMING AT VILLAGE OF BUKIT PENINJAUAN II SUKARAJA DISTRICT OF SELUMA REGENCY - Sarina sarina sarina (UNIVERSITAS LANCANG KUNING, 2020)
Sukaraja districts is one of the districts in Seluma regency as a rice producing area with planting area of ​​326 ha consists of 15 farmer groups. Village of Bukit Peninjaun II is one of the villages in Sukaraja ditrict where most of the people are rice farmers (65%) with planting area of ​​97 ha and consists of 5 farmer groups. The purpose of this research is to find out the cost of rice sale in Bukit Peninjaun II Village. This research is also to know the efficiency of wet land paddy farming in Bukit Peninjau II Village, Sukaraja district od Seluma regency. The study was conducted from March to July 2017 in Bukit Peninjauan II. Site selection is done purposively with consideration that Bukit Peninjaun II is a rice production center in Sukaraja sub-district of Seluma Regency. Sample consists of 22 people from 110 farmers of paddy rice (20%). The data analyzed are production cost, revenue and income, r / c ratio and basic nutrient. The results showed that the cost of selling rice in Bukit Penijauan II village was Rp.4.482,212 / kg well below market price. Rice paddy farming in Bukit Peninjau II village is efficient, seen from R / C ratio of> 1 that is 2.58. Kata Kunci : Cost, Eficiency, Rice BPII